Quantitative examination into the involvement of accountants in corporate strategy in malaysian public listed companies: a stewardhsip theory perspective - Annuar, Hairul Azlan; Ismail, Yusof; Olanrewaju, Aminu Sakiru (2012)
Purpose – The overall purpose of the research presented is to ascertain the extent and nature of accountants’ involvement in corporate strategy in Malaysian public listed companies (PLCs). Design/methodology/approach – The research employed the use of questionnaires to extract information from accountants and company secretaries to the board of directors of listed companies on Bursa Malaysia. Findings – The findings reveal that accountants in Malaysia are involved in both phases of corporate strategy, namely strategy formulation and evaluation respectively. It appears that their involvement is more toward advisory role in making sure the overall mission and objectives of the organizations are on track. At the formulation stage, accountants are involved even in the very initial stage of advising management with strategic proposals, directly helping to formulate proposals and even shaping the strategic framework, which ensure that only strategic proposals that lie within the current concept of strategy is submitted and deliberated. In the evaluation phase, accountants appear to impact on the criteria and timing of the evaluation of a strategy, and would source information for the evaluation from other top management team members prior to making their reports. Research limitations – Consistent with other management studies conducted in Malaysia, a low response rate was obtained despite adopting methods that would ensure high rate of return. This in turn may affect generalization of the research findings. Practical Implications – Findings from this research suggest that the involvement of accountants in different phases of corporate strategy is an indication that accountants are no longer giving too much a focus on management control. Although control is still a major issue in the accountants’ agenda, their strategic involvement may suggests that accountants are adequately meeting their responsibilities of providing long-term direction to their companies and also suggests that accountants are in a position to support and advice the board of directors effectively. Their active involvement is likely to result in successful strategic formalization and conclusion. Originality/value – There is a lack of work on studying accountants’ involvement in corporate strategy in developing countries, whereby previous work and literature review were predominantly based upon the experience of companies in the Western economies. Keywords: Accountant, corporate strategy, management, corporate governance, interview, public listed companies, Malaysia